Finite element simulation of miniaturized ZnO/Si SAW sensor for rapid detection of dichloromethane gas - Mohamad Razali, Nur Fatin; Md Ralib, Aliza Aini; Saidin, Norazlina (2018)
Air quality control is very crucial as poor air quality can lead to chronic respiratory organ diseases. Hence, detection of numerous toxic and hazardous gas is utmost significance. A low cost and high sensitivity gas sensor is crucial to monitor the excessive presence of the dangerous gas that can harm human’s health. In recent years, various type of gas sensors have been developed for various applications such as medicine, industry, automotive and environmental monitoring. One of the harmful gas is the dichloromethane gas. Dichloromethane (DCM) gas, CH2Cl2 is widely used in industry due to its organic characteristics. However, the excessive of the amount of the gas could bring harm to human’s health. Hence, a lot of sensing devices have been developed including surface acoustic wave (SAW) gas sensor. This paper presents the 2D finite element simulation of miniaturized ZnO/Si SAW gas sensor for rapid detection of DCM gas. Using a powerful finite element analysis software known as COMSOL Multiphysics, the gas sensor is modelled according to the specific criteria using 2D approach. The effect of different thickness of ZnO thin film as piezoelectric layer is investigated on the SAW propagation characteristics. The resonance frequency of simulated ZnO/Si SAW gas sensor is 300 MHz with wavelength of 11.67μm. The shift in frequency is the measurement used to measure the changes occured to sense the presence or absence of DCM gas. The shift of resonance frequency is observed in the absence and presence of dichloromethane gas. This work has high potential to realize single chip gas sensor due to its silicon compatibility for rapid detection of harmful gas for environmental monitoring.